Analysis and Training of Innovative Learning through the Use of the Irydium Application in Basic Chemistry Practicum - Ramadhani, Sitti Fatimah; Islam, Muhammad Fajar; Parubak, Apriani Sulu (Jurnal Inovasi Pembelajaran Kimia, 2025)
The development of technology in education, particularly in chemistry education, demands innovation in laboratory activities to enhance their effectiveness and efficiency. One such innovation is the Irydium Application, a digital-based platform for basic chemistry practicum. This study aims to determine the effectiveness of using the Irydium Application among students of the Chemistry Education Study Program who have completed the School Field Introduction Program (Pengenalan Lapangan Persekolahan/PLP). The research began with a training session on the use of the Irydium Application prior to data collection. A descriptive qualitative method was employed, with data collected through interviews, surveys, and observations to obtain a comprehensive understanding of the changes and impacts associated with the application’s use in basic chemistry practicum activities. The results show that the Irydium Application is highly needed by PLP students to support laboratory practices in schools. However, students were only introduced to this application after the training. Students also agreed that the Irydium Application is easy to install and operate, and it can significantly enhance the effectiveness of chemistry practicum activities in schools. Therefore, the integration of the Irydium Application can serve as an innovative and technology-based approach to improving chemistry learning and practicum experiences.